CORAL REEF FISHES IN THE COASTAL WATERS OF PHU YEN - Long, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2014)
Assessments of reef fish communities in the coastal waters of Phu Yen province were carried out at 11 sites in April 2009 by using SCUBA diving. Results from this study show that there were 210 species belonging to 96 genera and 39 families of coral reefs fishes recorded, of which wrasses (Labridae: 37 species), damselfishes (Pomacen-tridae: 36 species), butterflyfishes (Chaetodontidae: 25) and surgeonfishes (Acanthuridae: 12 species) were recorded with higher number of species. Target fishes belonging to groupers, snappers, sweetlips, leatherjackets, triggerfishes and moray eels were rare in composition and number of species. Density of fishes at each studied site was relatively low, giving mean value being 93.8 inds./100m2, mostly dominated by fish at size class of 1-10cm belonging to butterflyfishes, damselfishes, wrasses, surgeonfishes and angelfishes (> 75%). Densities of target fishes with large sizes of groupers, snappers, sweetlips, emperors were very low (< 0.5 inds./100m2) and this indicates that resources of fishes were over-exploited. Sites at Vinh Hoa (Cu Mong lagoon), Tu Nham (Xuan Dai bay), Bai Nam (Cu Lao Mai Nha), Hon Chua (An Chan) and Hon Nua (Vung Ro) supported a higher number of species and densities of reef fishes compared to other sites in the coastal waters of Phu Yen province.